Is the Effect of Procedural Justice on Police Legitimacy Invariant? Testing the Generality of Procedural Justice and Competing Antecedents of Legitimacy - Kaminski, Robert (2016)
Objectives This study tests the generality of Tyler’s process-based model of policing by examining whether the effect of procedural justice and competing variables (i.e., distributive justice and police effectiveness) on police legitimacy evaluations operate in the same manner across individual and situational differences. Methods Data from a random sample of mail survey respondents are used to test the “invariance thesis” (N = 1681). Multiplicative interaction effects between the key antecedents of legitimacy (measured separately for obligation to obey and trust in the police) and various demographic categories, prior experiences, and perceived neighborhood conditions are estimated in a series of multivariate regression equations. Results The effect of procedural justice on police legitimacy is largely invariant. However, regression and marginal results show that procedural justice has a larger effect on trust in law enforcement among people with prior victimization experience compared to their counterparts. Additionally, the distributive justice effect on trust in the police is more pronounced for people who have greater fear of crime and perceive higher levels of disorder in their neighborhood. Conclusion The results suggest that Tyler’s process-based model is a “general” theory of individual police legitimacy evaluations. The police can enhance their legitimacy by ensuring procedural fairness during citizen interactions. The role of procedural justice also appears to be particularly important when the police interact with crime victims